La Festiva trompa al célebre aparatoso recibimiento del excelentísimo señor don Ricardo Fanshau, dignísimo embajador de Inglaterra a España (1664), de José Román de la Torre y Peralta: texto e introducción - Sánchez Jiménez, Antonio; López Lorenzo, Cipriano (Santiago de Compostela: Andavira, 2022)
Critical edition of José Román de la Torre Peralta description of the visit of the English ambassador to Seville
Keywords: Golden Age Spanish Poetry; Gardens